Development of instant rice porridge with tripe (instant goto) - Mauricio. Rosela A.; Azanza, Ma. Patricia V. (1999.)
Goto is one of the all-time favorite snacks of Filipinos. However, goto is not an easy to prepare snack because the preparation of meat component alone is more than 1 h even with the aid of a pressure cooker. This study developed a formulation for instant rice porridge with tripe or goto. The formulation of the rice porridge with tripe was selected from published Filipino recipe books by Perez (1972), Daza (1974), and Fabian (1969) using the Consumer Acceptability Test. The selected recipe for goto was by Fabian (1969). Improvement in the Fabian (1969) recipe was done by decreasing the amount of the fish sauce by 50% of the original amount. The components of the porridge were dehydrated separately. The Head Malagkit Sunsong rice was hydrated in 0.5% CaCl2 solution for 30 min; gelatinized for 6 min with steam under pressure at 121.5°C; and dehydrated for 55 min in a forced air convective dryer at 55°C. The dehydrated rice was puffed by immersing in 200°C vegetable oil for 2 sec. The instant tripe was prepared by treating with 5% lye-phosphate solution for 3 min then cooking it with steam under pressure at 121.5°C for 40 min. The tripe cut was 1x2cm^2 with 1-mm thickness and dried in a forced air convective dryer with 65°C for 2 h. The spring onions were steam blanched for 2 min before drying at 55-60°C for 1.75 h. The instant broth was prepared by compounding salt, sugar, shortening, chicken fat, SSF 120/k, 1.2321 L Meat flavoring, onion powder, garlic powder, pepper, oleoresin ginger, and modified starch. The rehydrated compounded instant goto was evaluated by 50 panelists using Consumer Acceptability Test against the standardized formulation of goto prepared using conventional cooking. The rehydrated instant goto was described as with cream to yellow rice base color, soft to neither soft nor tough rice texture, slightly thick consistency, moderate to distinct aroma and flavor, brown to cream tripe color, neither soft nor tough tripe texture. The overall acceptability of the rehydrated instant product was between like slightly to moderately and was not significantly different from the standardized formulation at 5% level of significance. The pH values of the compounded and rehydrated instant product samples were 5.8 and 6.02 respectively. The Aw values were determined to be 0.46 and 0.98 respectively. The TPC of the compounded and rehydrated product were 3.0 x 10^4 cfu/g and 2.16 x 10^6 cfu/g and the YMC were both <10^2 cfu/g. Cost analysis showed that the cost of the developed product was estimated to be P18.00 per serving of 46 g dry weight. The commercially available instant goto with the same packaging and serving portion costs P15.25. There is P2.75 difference in the costs of the two instant products that could be attributed to the different ingredients used. The results of this study can be used in the commercial production of instant goto, and as a basis for the development of other rice-based products. Some recommendations for the improvement of the product included improvement of method of dehydration of tripe, improvement of flavor and consistency of the product, selection of proper packaging material and storage study of the product.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Congee